EFL Students’ Engagement on the Lecturer’s Global Comments as Written Corrective Feedback in Undergraduate Thesis Coursework - Hapsari, Astri; Gunawan, Fahmi; Qudsyi, Hazhira (PANYONARA: Journal of English Education, 2025)
Although there have been studies discussing written corrective feedback, there are still limited studies exploring how students engage with the written corrective feedback (WCF), especially the lecturer's global comments as WCF in the context of the EFL undergraduate thesis writing process. This interview study discusses students' engagement with the lecturer's global comments as written corrective feedback. Four students participating in undergraduate thesis coursework agreed to participate in this study. Data were mainly collected through interviews. The study indicates that the students demonstrated affective engagement, like becoming more patient and satisfied with their drafts, confident with their writing, and responsible with their tasks. They also demonstrated behavioural engagement, such as responding to feedback regularly and becoming more consistent with the content. They also show cognitive engagement, such as being more attentive, detailed, and focused in the coherence of citations and references with background, research questions, and methodology, and grammatical accuracy, based on the lecturer's feedback on the process of writing an undergraduate thesis. However, the findings in this study are still limited to identifying the types of engagement from the lecturer's global comments as WCF. Future research may include more deliberative discussion on localised comments and surface versus deep-level awareness of WCF.